ANALISIS STRATEGI DINAS KEBUDAYAAN PARIWISATA, PEMUDA DAN OLAH RAGA DALAM PENGEMBANGAN PARIWISATA DI KABUPATEN PONOROGO: JURNAL TESIS - HS, Binarpendyah Rawitri; Pramono, Joko; Haryanto, Aris Tri (JI@P, 2023)
The results of the study show the S-O Strategy, which is to develop and increase tourist attraction with various potentials, such as the typical socio-cultural conditions of the community. S-T strategy, by utilizing good information media to attract investors. This is done by providing accurate information about the leading potential of tourism. W-O strategy, namely with stable political conditions, it is hoped that the Culture and Tourism Office will be able to involve power holders so that they are willing to provide assistance in improving human resources both in quality and quantity. Threats are facilities and infrastructure that are tools to support the success of an effort process carried out in public services, because if these two things are not available then all activities carried out will not be able to achieve the expected results according to the plan. Keywords: Tourism development strategy of the Department of Culture, Tourism, Youth and Sports, Ponorogo Regency